Effect of environmental temperature and diet on the digestive response of red-footed tortoise Chelonoidis carbonaria hatchlings - Mendoza, Pierina [UNESP] (2022)
Temperature effect on digestive response is still unknown in most reptile species as is the case with the red-footed tortoise (Chelonoidis carbonaria). Hatchlings were fed with two diets, one high in fiber (14.16% crude fiber, 39.20% neutral detergent fiber dry matter basis, DMB) and one high in starch (27.71% DMB), housed at 30 degrees C or 20 degrees C, to evaluate the temperature effect on food intake (FI), digesta passage, apparent digestive efficiency (Da), and growth. At 30 degrees C the animals showed higher FI and digestible energy (DEI), as well as metabolic mass-specific intake of digestible nutrients and energy (DEImm, 99.48 +/- 14.30 versus 43.18 +/- 17.26 kJ kg-0.86 day-1; P<0.001); daily gain (0.98 +/- 0.26 versus 0.32 +/- 0.11 g day-1; P<0.001), and growth of carapace length (0.25 +/- 0.05 versus 0.09 +/- 0.02 mm day-1; P<0.001) and width (0.15 +/- 0.03 versus 0.05 +/- 0.01 mm day-1; P<0.001). DEI at 30 degrees C was expressed: (R2=0.67). Non-diet effect was observed on digesta passage, however, at 20 degrees C the transit (5.50 +/- 1.36 versus 3.60 +/- 1.05 days; P<0.01) and retention times (13.80 +/- 1.29 versus 8.90 +/- 1.15 days; P<0.001) were longer than at 30 degrees C. Animals housed at colder conditions also presented lower gut content (30.39 +/- 13.39 versus 40.45 +/- 9.76 g Kg-1; P<0.05) and gut fill time (0.08 +/- 0.01 versus 0.02 +/- 0.01 g day-1; P<0.001). Da were similar between temperatures but due to the diet effect, hatchlings fed the high starch diet presented higher DM and energy coefficients. Environmental temperature influences the digestive response and growth of C. carbonaria. Overall digestive efficiency was temperatureindependent but rather influenced by diet quality and composition.